2019
DOI: 10.1016/j.jjcc.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Simple risk model and score for predicting of incident atrial fibrillation in Japanese

Abstract: We developed 7-year risk scores for incident AF using usually available clinical factors including ECGs in primary care. These risk scores could identify individuals with high risk of incident AF at health check-up and outpatient clinics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…All studies used the C-statistic to assess model discrimination for incident AF within their cohorts. Nine studies assessed calibration by providing both a P -value for a goodness-of-fit test and a calibration plot in at least one of the risk models that these studies reported on refs, 20 , 21 , 24 , 27 , 29 , 30 , 32 , 36 , 40 seven studies assessed calibration only by a P -value for goodness-of-fit test, 22 , 26 , 35 , 39 , 41 , 43 , 44 two studies assessed calibration only by a calibration plot, 25 , 33 and nine studies reported neither of these calibration parameters. 23 , 28 , 31 , 34 , 37 , 38 , 42 , 45 , 46 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All studies used the C-statistic to assess model discrimination for incident AF within their cohorts. Nine studies assessed calibration by providing both a P -value for a goodness-of-fit test and a calibration plot in at least one of the risk models that these studies reported on refs, 20 , 21 , 24 , 27 , 29 , 30 , 32 , 36 , 40 seven studies assessed calibration only by a P -value for goodness-of-fit test, 22 , 26 , 35 , 39 , 41 , 43 , 44 two studies assessed calibration only by a calibration plot, 25 , 33 and nine studies reported neither of these calibration parameters. 23 , 28 , 31 , 34 , 37 , 38 , 42 , 45 , 46 …”
Section: Resultsmentioning
confidence: 99%
“…Significant improvement was demonstrated in CHARGE-AF (Cohorts for Heart and Aging Research in Genomic Epidemiology) with addition of the P-wave axis 35 and brain natriuretic peptide (BNP) and/or C-reactive protein (CRP), 41 in the FHS-AF 10-year model with addition of BNP and CRP, 39 and in the Seirei model with addition of ECG parameters to the model. 27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Summary measures of association were reported as RRs with 95% CIs. Except for one study [24], all studies categorised physical activity exposure (e.g., leisure-time physical activity, intensity of physical activity, or total or any physical activity) into two or more groups. Risk estimates could not be transformed to consistent comparisons (e.g., top versus bottom thirds of the distribution of physical activity) using standard statistical methods previously described [25,26] because of the varying reporting of outcomes.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…he analysis of previously examined TAF risk factors [4,5,[7][8][9][10][11][12][13][14][15][16][17][18][19] and non-thyrotoxic AF rediction tools [28, [31][32][33][34] helped to define input variables for our models. First, we built everal intermediate models, including more than 30 variables.…”
Section: Input Variablesmentioning
confidence: 99%